(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In the current office environment, office personnel are using computers for long periods of time on a daily basis. Consequently, there have been increased reports of work-related neck and upper limb musculoskeletal disorders and tension neck syndrome, which affect countless office workers who use computers, which is also the leading cause of occupational illnesses. In rehabilitation treatment, clavicle support that involves the use of elastic material is prescribed to exert corrective pulling forces at the upper back and stabilise the clavicle and shoulder movements. This study therefore aims to evaluate the effect of clavicle support on the myoelectric activity of the axioscapular group of muscles, including the Anterior Deltoid (AD), Upper Trapezius (UT), Middle Trapezius (MT), and Lower Trapezius (LT) in young women who experience chronic neck and shoulder pain during computer use. The results indicate that there is an overall significant difference in the percentage of maximum voluntary electrical activation (MVE%) of the axioscapular group of muscles between the use and absence of clavicle support (t = -2:982, p = 0:005 ‹ 0.05). Amongst the four types of muscles studied, the use of clavicle support has significant effects on the MT and UT muscles. The results is important to improve our understanding of clavicle support in association with muscle activity, thereby providing the basis for prescribing suitable rehabilitation treatment and intervention devices in the workplace for the reduction of musculoskeletal disorders.